Selling to the cities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Thanks to rapid urban expansion in ACP States, farmers are shipping more and more food to capital cities, and towns. This could be a great stimulus to agricultural production ? as long as the supply chain from harvest-time to meal-time (storage,...